Analisis Kemampuan Adaptasiusaha Mikro, Kecil, dan Menengah terhadap Digitalisasi - Aulia Putri Siagian; Siti Marfuah Bako; Muhammad Faisal Haririe Nasution; Imam Fitrahwan; Siti Suaibah Nsution (Kajian Ekonomi dan Akuntansi Terapan, 2025)
In the era of globalization and the Fourth Industrial Revolution, Micro, Small, and Medium Enterprises (MSMEs) face significant challenges to remain relevant and competitive, one of which is through digital adaptation. However, digital adaptation among MSMEs still encounters various obstacles, especially in using food delivery platforms such as GoFood and GrabFood, including high commission fees, unilateral order cancellations, and slow technical responses. This study aims to analyze the adaptability of MSMEs to digitalization and its impact on business sustainability and performance amid the digital economic transformation. This research applies a qualitative phenomenological approach involving MSME actors from various business sectors. Data were collected through interviews and observations to explore the lived experiences of MSME actors in facing digital challenges. The results indicate that the success of MSME digital adaptation depends not only on internal capabilities but also on external support from platform providers and the government. Synergy among business actors, digital service providers, and policymakers is essential to create an inclusive and sustainable digital ecosystem for MSMEs.